Pengaruh Profitabilitas dan Leverage terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sektor Industri Properti dan Real Estate Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2023 - Zikri D, Alvi; Nelvirita (Jurnal Nuansa Karya Akuntansi, 2025)
The purpose of this research is to analyze the effect of profitability and leverage on firm value in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Firm value in this study is measured using Price to Book Value (PBV), profitability is measured by Return on Assets (ROA), and leverage is measured by Debt to Equity Ratio (DER). The research method employed is a quantitative approach using secondary data obtained from the annual reports of companies listed on the IDX over the observation period. Data analysis techniques utilized multiple linear regression analysis with the assistance of SPSS software.The results of this study indicate that profitability has a positive and significant effect on firm value. This finding suggests that higher profitability levels tend to increase firm value, as companies capable of generating stable profits are more attractive to investors. Conversely, leverage does not have a significant effect on firm value. This implies that the level of debt owned by companies is not the main consideration for investors in assessing firms in the property and real estate sector.This study is expected to provide useful insights for company management and investors in making investment decisions and managing optimal financial structures. Additionally, this research contributes to the development of financial theory, particularly regarding the factors that influence firm value in the property and real estate industry.